2021
DOI: 10.3390/app11115202
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Effects of Fermented Feed Supplementation on Growth Performance, Carcass Characteristics, and Meat Quality of Hanwoo Steers during the Early and Late Fattening Period

Abstract: The present study was conducted to determine the effects of formulated feed (IRG: Italian ryegrass, WCC: whole crop corn, and fermented feed) on growth performance, carcass characteristics, and meat quality of Hanwoo steers during early and late fattening periods. Twelve Hanwoo steers were randomly assigned into two groups: control and treatment (n = 6/group). The control group received rice straw with concentrate; the Treatment group received formulated feed for 13 months. Results revealed that formulated fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…The energy requirement of dairy breed animals, e.g., Holstein Friesian in this study, relative to their weight, is expected to be high because they have more active internal organs and fat depots necessary to sustain their milk production than dairy cows [1]. In addition, other studies have reported that daily weight gain decreased in the late fattening stage even though feed and energy intake is like those in the early fattening stage because they require higher maintenance energy during the late fattening stage [19,28]. Previously, no significant difference in daily gain in dairy on beef crossbred compared with purebred Holsteins [1,11] was reported.…”
Section: Growth and Carcass Traitsmentioning
confidence: 86%
“…The energy requirement of dairy breed animals, e.g., Holstein Friesian in this study, relative to their weight, is expected to be high because they have more active internal organs and fat depots necessary to sustain their milk production than dairy cows [1]. In addition, other studies have reported that daily weight gain decreased in the late fattening stage even though feed and energy intake is like those in the early fattening stage because they require higher maintenance energy during the late fattening stage [19,28]. Previously, no significant difference in daily gain in dairy on beef crossbred compared with purebred Holsteins [1,11] was reported.…”
Section: Growth and Carcass Traitsmentioning
confidence: 86%
“…The number of duplicates had a practical effect on inference errors in analyzing differences of means or variances [20]. In the Independent sample t-test, the minimum number of replications used was six replications [4,21]. In contrast, for a large number of replications, Fauzyah et al [22] and Chang et al [23] used 18 and 50 replications, respectively.…”
Section: Advances In Biological Sciences Research Volume 18mentioning
confidence: 99%
“…One of the feed technology methods that can improve cattle performance is by using fermentation. It is a process that is essential in the usage of prospective nutrients in maximizing their conservation and minimizing antinutritional compounds in the feed process [4]. The fermentation technique can inhibit microbial pathogens' growth and increase concentrates' nutrient quality [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on developing feeds with high-energy and high-protein content to decrease beef production costs in Korea by shortening the raising period of Hanwoo steers [1,2]. The protein content of lupin has been reported to vary between 32% to 55%, depending on the processing method [3][4][5].…”
Section: Introductionmentioning
confidence: 99%